Stability analysis of thin-walled composite plate in unsymmetrical configuration subjected to axial load - Falkowicz, Katarzyna; Debski, Hubert (Thin-walled structures, 2021)
The subject of the study were thin plate elements with a central cut-out of regular shapes, made of carbon-epoxy composite, subjected to uniform compression. The purpose of the analysis was the possibility of using such elements as elastic elements, which stiffness can be designed by changing the geometric parameters of the cut-out and by the appropriate configuration of the composite layers layout. To ensure the stable work of the structure in the postcritical range, in the plate construction an unsymmetrical composite layer layout was used, having selected B matrix couplings, described in i.a. by York and Altenbach. For the adopted solution, a numerical analysis of the structure using the finite element method was carried out. The scope of numerical simulations included linear analysis of eigen problem and calculations using geometrically non-linear procedures. The numerical tool used in research was the ABAQUS® program. Experimental studies were carried out on an universal testing machine using the optical ARAMIS system. The purpose of the calculations was to select the laminate layer layout ensuring the lowest flexural-torsional buckling form, ensuring stable work of the structure in the postcritical range. •The influence of the layer arrangement on buckling load and post-buckling behavior of composite plates have been investigated.•The influence of the cut-out geometric parameters on buckling load and post-buckling behavior of composite plates have been investigated.•A nonlinear stability problem were solved.•The possibility of using thin plate elements as elastic elements was investigated.•The numerical models were verified in experimental tests.